How Does AI Improve Pediatric Disease Diagnosis? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2016)
Artificial intelligence (AI) is rapidly transforming various sectors, and healthcare is no exception. In pediatrics, AI is emerging as a powerful tool to aug...
Keywords: AI in Pediatrics; Improve; Pediatric; Disease; Artificial Intelligence; Machine Learning; Deep Learning